Concentration of heavy metals in the blood plasma of grazing-cattle of the smelter in Mitrovica - Krasniqi-Cakaj, I; Krasniqi, B; Gavazaj, F; Kurtaj-Bajrami, B; Selimi, Q (Journal of the Hellenic Veterinary Medical Society, 2025)
The accumulation of heavy metals in animals depends on the concentration in the soil, pasture, duration of exposure and the way of absorption of metals into the blood and other tissues. The aim of the research is to identify the level of lead (Pb), and some heavy metals in the blood plasma of cattle, as a bio-indicator of exposure to pollutants and determine the toxic index of pollution. The determination of the level of metals was carried out in 73 samples of blood plasma of cattle, in 4 locations at different distances from the smelter (2km, 3km, 5km and 40km - controls). The results show the highest level of heavy metal exposure in: location 1 Pb is (0.571 ppm), Cu (1.327 ppm) and Fe (6.376 ppm), while in the control location, there is a lower level of concentration in Pb (0.264 ppm), Cu (0.568 ppm) and Fe (2.363 ppm), compared to the others. The average values plasma Fe in location 1 (6.376 ppm) and 2 (5.946 ppm), is relatively small (Dif.=0.43 ppm), in location 3 there is a moderate decrease compared to the others and the control. Location 1 consistently shows the highest HPI values ​​for all three heavy metals in bovine plasma, indicating higher exposure to pollutants (Pb, Cu and Fe). There are significant differences in the levels of Cu contamination between locations (F statistic = 11.214, p < 0.0001). The average values ​​of Cd, Zn and Hg, in the 3 locations near the smelter and in location 4, are below the detection level. The research results confirm that: no matter how high or low the concentration values ​​of heavy metals in the blood plasma are, they present negative effects on exposed organisms even after two decades from the closure of the smelter. Heavy metal pollution, especially lead (Pb), in long-term-chronic exposure environments, endangers animal and human health.